Pengembangan E-ModulKontekstual pada Pembelajaran IPA (Fisika) untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Yersi; Muhammad Arsyad; Pariabti Palloan (Jurnal Penelitian Pendidikan IPA, 2025)
This research is a type of research and development (R&D) using the 4D model: define, design, develop, and disseminate. The goal of this research and development is to find out the content validity, practitioners’ responses, and the effectiveness of using a contextual e-module in science (physics) learning to improve students’ critical thinking skills. The content validity of the e-module was evaluated by 3 experts. Its practicality was evaluated by 10 science teachers who teach physics. The e-module was tested on 45 eighth-grade students at SMP Katolik Sudiang, where the researcher teaches. The instruments used in this study included a validation sheet for the e-module, a validation sheet for the practitioners’ response questionnaire, and a critical thinking test validation sheet. Each instrument was validated by experts. The practitioners’ questionnaire and the critical thinking test were also used in the study. The results showed that the contextual e-module in science (physics) learning was valid according to the experts, very practical according to the practitioners’ responses, and effective in improving students’ critical thinking skills, with an N-Gain percentage of 60.85%. Based on the results, the developed e-module is considered valid, very practical, and effective in improving students' critical thinking skills.